ANALISIS PELAYANAN PUBLIK PADA BAGIAN PROTOKOL DAN KOMUNIKASI PIMPINAN DAERAH KABUPATEN BARITO KUALA - Irawanto; Aulia Rosyadi; Akhmad Abdurahman; Bahtiar; Anhar Yani (Jurnal PubBis, 2024)
According to the community, services in the protocol and communication section of the Barito Kuala Regency Regional Leaders are not optimal, so activities involving regional leaders sometimes experience delays and can have an impact on the government's image. This study aims to determine and analyse how information and protocol services in the Protocol and Communication Section of Regional Leaders reach the community. The research approach used is qualitative. The data sources were five people. Data were collected through interviews and documentation. The collected data and information were analysed qualitatively based on narratives. The results showed that community services, information services, and protocol had been carried out, both directly and through the mass media. These service activities are always coordinated with regional apparatus organizations on an ongoing basis, and negotiations are carried out with interested communities so that these service programs are more effective. This research shows that maximum service has implications for building a better government image. Keywords: Public services, community services, information services and protocols